Synthesis and Properties of Sulfhydryl-Reactive Near-Infrared Cyanine Fluorochromes for Fluorescence Imaging - Yuhui Lin; Ralph Weissleder; Ching-Hsuan Tung (Molecular Imaging)
Near-infrared fluorochromes (NIRF) are useful compounds for diverse biotechnology applications and for in vivo biomedical imaging. Such NIRF must have high quantum yield, be biocompatible, and be conjugatable to a wide variety of proteins, peptides, and other affinity ligands. Here, we describe the synthesis of four new nonsymmetrical sulfhydryl-reactive cyanine NIRF with excellent optical and chemical properties. Each fluorochrome was designed to contain an iodoacetamido group that reacts specifically with sulfhydryl-containing molecules. The synthesized fluorochromes were used to label model peptides and sulfhydryl-containing biomolecules.